The role and importance of the command in educating cadets on the basis of spiritual and moral values in higher military educational institutions - Qodirova Feruza Mamurovna (Zien Journals, 2022)
This article is about the role of command in moral and moral education of cadets studying in higher military educational institutions and the role of command in raising cadets to become well-rounded, highly moral people
Keywords: military personnel; educational level; personal and active approach